Diagnosis of Students’ Learning Difficulties Eye Studying Development Participant Educate - Dwi Putri, Febri; Ayundaliani Harahap, Silvi (International Journal of Students Education, 2024)
Learning difficulties are a fear that students often face Student Development lecture. Learning difficulties experienced by students in This subject is also an important problem in the world of education. this journal aims to diagnose students’ learning difficulties in this course by identifying causal and developing factors appropriate strategy by overcoming learning difficulties. This research uses a quantitative approach involving students who take Student Development courses. Method used in this research using literacy methods. The results of this research are in get it through analysis data And opinion para expert. Study show that Most students experience learning difficulties including not understanding concepts, ineffective application of theory, lack of critical thinking skills, low motivation and lack of support from lecturers, as well as internal weaknesses analytical skills become factor main Which influence difficulty Study student. Should in in learning involve strategy teaching Which can help student For overcoming learning difficulties, such as using active learning methods, emphasis on understanding concepts, and providing constructive feedback. Diagnose difficulties Study is step important in identify And overcome problem Study student. Lecturers need to provide attention especially for students who experienced difficulty Study, do approach learning Which interactive And deep, providing appropriate support and guidance, collaboration between students and lecturers, apply effective teaching methods, and provide continuous training to overcome learning difficulties. This research can be a basis for development strategy Which more effective in eye studying Development Participant Educate.